A wear-resistant, self-cleaning anti-reflection film and a preparation method thereof
By surface-modifying SiO2 nanoparticles and combining them with organic resin, an anti-reflective film that is resistant and self-cleaning is prepared, solving the problems of poor wear resistance and low self-cleaning performance of the existing coating, and achieving high light transmittance, good mechanical properties and self-cleaning performance.
Patent Information
- Application Number
- CN202410541539.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-30
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-04-30
AI Technical Summary
The anti-reflective coatings prepared from existing SiO2 nanoparticles have poor wear resistance and low self-cleaning performance, and improving one of these functions often impairs the other.
Through surface modification, SiO2 nanoparticles are changed into hydrophobic particles and combined with organic resin to form SiO2 sol, and coated on a glass substrate to form an anti-reflective film.
It has achieved excellent anti-reflection performance, good mechanical properties and self-cleaning performance of the coating, and has great application potential.
Smart Images

Figure CN118359384B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of optical films, and in particular to a wear-resistant, self-cleaning anti-reflection film and a preparation method thereof. Background Art
[0002] Glass is transparent to both visible and near-infrared light and can be used in electronic displays, solar cell covers, architectural glass, etc. Typically, glass can reflect up to 8% of incident light on both sides, which is undesirable for any optical device that needs to reduce reflection. Therefore, coating the glass surface with an anti-reflection film is necessary to further improve the performance of optical devices.
[0003] With the widespread application of anti-reflection films in the optical field, there are more and more methods for preparing anti-reflection films, such as magnetron sputtering, chemical deposition, sol-gel method, etc. Among them, the preparation of SiO2 coatings by sol-gel method has attracted increasing research interest due to its advantages such as rich material sources, simple operation and low cost. This method usually uses tetraethyl orthosilicate as a precursor and ammonia water as a catalyst at room temperature to synthesize SiO2 nanoparticle sol with adjustable size, and then coats it on the substrate to achieve anti-reflection function. The coating obtained by this method has a low refractive index, which can often make the glass substrate obtain a transmittance close to 100% at a specific wavelength.
[0004] However, there are two problems that greatly limit its application. First, the nano-SiO2 coating is composed of randomly stacked nanoparticles, and there is no strong bond between the particles, resulting in poor wear resistance of the coating. Second, the anti-reflection film is easily contaminated by dust in the air when used in outdoor conditions, which reduces its anti-reflection performance.
[0005] Although many methods have been reported to improve wear resistance and self-cleaning properties, in most cases, improving one function will impair the other. Therefore, it is of great significance to prepare anti-reflection films that have both good wear resistance and self-cleaning properties.
[0006] The present invention uses a surface modification method to modify SiO2 nanoparticles into hydrophobic particles, then adds an organic resin as a binder to prepare a SiO2 sol, and applies the sol on a glass substrate to form an anti-reflection film. The coating exhibits excellent anti-reflection performance and can make the transmittance of the glass substrate at 580nm reach 99.1%. At the same time, the coating has good mechanical properties and self-cleaning properties, and has great application potential. Summary of the invention
[0007] The present invention provides a wear-resistant, self-cleaning anti-reflection film and a preparation method thereof to overcome the technical problems of poor mechanical properties and low self-cleaning performance of anti-reflection coatings prepared from SiO2 nanoparticles. In the present invention, SiO2 nanoparticles are modified into hydrophobic particles by surface modification, and then an organic polymer is added as a binder to form a SiO2 sol, which is then coated on a glass substrate to form an anti-reflection coating. Hydrophobic SiO2 nanoparticles can make the coating have good self-cleaning properties. Organic polymers can connect SiO2 nanoparticles together to improve the wear resistance of the coating. This has high light transmittance, good mechanical properties and self-cleaning properties. The specific technical scheme is as follows:
[0008] A method for preparing a wear-resistant, self-cleaning anti-reflection film comprises the following steps:
[0009] S1. Synthesis of hydrophobic SiO2 nanoparticles: SiO2 nanoparticles are prepared by hydrolysis polymerization using tetraethyl orthosilicate as a silicon source, anhydrous ethanol as a solvent, ammonia water as a catalyst, and hexamethyldiazaine as a hydrophobic modifier, and then the hexamethyldiazaine hydrophobic modifier is added and stirred for 3-6 hours, and then aged at room temperature for 7-14 days. Finally, hydrophobic SiO2 nanoparticles are obtained by centrifugation;
[0010] S2, preparing sol: dispersing the hydrophobic SiO2 nanoparticles obtained in step S1 in a mixed solvent of isopropanol and methyl isobutyl ketone, stirring evenly, adding pentaerythritol triacrylate and hydroxycyclohexyl phenyl ketone, and stirring evenly to obtain a composite sol;
[0011] S3, coating: the composite sol obtained in step S2 is coated on the glass substrate, and the thickness of the coating is controlled according to the pulling speed of the immersion coating apparatus. After the coating is completed, the glass sample is placed in an oven for drying. Finally, the sample is placed in a N2 purge chamber to make the O2 concentration lower than 100 ppm, and 400 mJ / cm 2 UV curing coating.
[0012] Preferably, the amounts of tetraethyl orthosilicate, ammonia water, anhydrous ethanol and hexamethyldiazaalkane added in step S1 are 5-15 parts by mass, 1-5 parts by mass, 60-100 parts by mass and 10-30 parts by mass, respectively.
[0013] Preferably, the amounts of the hydrophobic SiO2 nanoparticles, isopropanol, methyl isobutyl ketone, pentaerythritol triacrylate and hydroxycyclohexyl phenyl ketone added in step S2 are 1-4 parts by mass, 20-50 parts by mass, 10-30 parts by mass, 0.01-0.5 parts by mass and 0.01-0.2 parts by mass, respectively.
[0014] Preferably, the thickness of the coating layer controlled in step S3 is between 80 and 140 nm.
[0015] Compared with the prior art, the present invention has the following beneficial effects:
[0016] (1) The anti-reflection coating prepared by SiO2 nanoparticles has excellent anti-reflection performance, but the coating has poor wear resistance and low self-cleaning performance. In addition, many methods have been reported to improve wear resistance and self-cleaning functions, but in most cases, improving one function will damage the other. In the present invention, the prepared coating not only has excellent anti-reflection performance, but also has both wear resistance and self-cleaning performance.
[0017] (2) In order to improve the wear resistance of the coating, the size of the nanoparticles can generally be reduced to make the coating denser. However, particles that are too small have poor stability and are easy to agglomerate. There is also a method of connecting the nanoparticles to each other through high-temperature treatment, but this method is only suitable for high-temperature resistant substrate materials. In the present invention, SiO2 nanoparticles are connected by organic polymers, and there is no need to synthesize particles of smaller size, and the coating can be prepared at low temperatures.
[0018] (3) Generally, when SiO2 sol is compounded with other polymers, the stability of the sol will be reduced. However, in the present invention, SiO2 sol is compounded with organic monomers, coated into a coating, and then formed into a polymer by photoinitiation. This method can avoid the influence of the polymer on the stability of SiO2 sol. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 Fourier infrared spectra of SiO2 nanoparticles before and after modification in a specific embodiment of the present invention;
[0020] Figure 2 (a) is a transmission electron microscope photo of SiO2 nanoparticles prepared in Comparative Example 2, Figure 2 (b) is a scanning electron microscope photograph of the SiO2 nanoparticle coating prepared in Comparative Example 2;
[0021] Figure 3 (a) is a transmission electron microscope photograph of the sol prepared in Example 1, Figure 3 (b) is a scanning electron micrograph of the coating prepared in Example 1;
[0022] Figure 4 1 is a transmittance spectrum diagram of the anti-reflection films prepared in Example 1, Example 2 and Example 3;
[0023] Figure 5 (a) and (b) are respectively the scratches of a 3H hardness pencil on the coatings prepared in Comparative Example 2 and Example 1 observed under an optical microscope;
[0024] Figure 6 These are the water contact angle test results of the coatings prepared in Comparative Example 1, Comparative Example 2, Example 1, Example 2 and Example 3. DETAILED DESCRIPTION
[0025] The present invention prepares SiO2 nanoparticles by hydrolysis polymerization reaction. Generally, there are a large number of -OH groups on the surface of SiO2 nanoparticles, and these groups easily absorb water vapor and dust in the air in the coating. The present invention modifies SiO2 nanoparticles by hexamethyldiazaalkane to make -O-Si(CH3)3 replace -OH, such as Figure 1 The Fourier infrared spectrum shows that -O-Si(CH3)3 exists in the modified SiO2 nanoparticles. This group can make the SiO2 nanoparticles hydrophobic, and the coating prepared from such particles is hydrophobic, which can make the coating have self-cleaning function.
[0026] In addition, the coating prepared by nanoparticles has poor wear resistance, and this is because particles are independent of each other and easily fall off. In the present invention, by hydrophobic SiO2 nanoparticles are dispersed in isopropyl alcohol and methyl isobutyl ketone mixed solvent, and then pentaerythritol triacrylate and hydroxycyclohexyl phenyl ketone are added. Earlier with SiO2 nanoparticles are dispersed in solvent, SiO2 nanoparticles can be avoided to reunite. And adding pentaerythritol triacrylate and hydroxycyclohexyl phenyl ketone, rather than directly adding resin, can avoid the influence of long-chain molecules on sol state. And the coating of application, under ultraviolet light curing, can be transformed into organic polymer, thereby make SiO2 nanoparticles link together, thereby improve the wear resistance of coating.
[0027] For anti-reflection film, the thickness and refractive index of the coating are crucial. Four times the product of the coating thickness and the refractive index is the optimal anti-reflection position of the coating. The wavelength of visible light is generally between 400 and 780 nm, which limits the thickness of the coating. The coating thickness is controlled within 80 to 140 nm, within which the best anti-reflection effect can be obtained.
[0028] The present invention will be further described below in conjunction with embodiments and comparative examples.
[0029] This comparative example provides a method for preparing an unmodified SiO2 nanoparticle coating, comprising the following steps:
[0030] S1, using 10 parts by mass of tetraethyl orthosilicate as a silicon source, 80 parts by mass of anhydrous ethanol as a solvent, and 2 parts by mass of ammonia water as a catalyst, to prepare a SiO2 nanoparticle sol by hydrolysis polymerization reaction;
[0031] S2, coating: coating the SiO2 nanoparticle sol obtained in step S1 on the glass substrate, and controlling the coating thickness to be 110 nm according to the pulling speed of the immersion coating apparatus. After coating, the glass sample is placed in an oven for drying.
[0032] This comparative example provides a method for preparing a hydrophobic SiO2 nanoparticle coating, which specifically comprises the following steps:
[0033] S1, using 10 parts by mass of tetraethyl orthosilicate as a silicon source, 80 parts by mass of anhydrous ethanol as a solvent, and 2 parts by mass of ammonia water as a catalyst, preparing a SiO2 nanoparticle sol by hydrolysis polymerization, then adding a hexamethyldiazaalkane hydrophobic modifier, stirring for 3 hours, and then aging at room temperature for 7 days to obtain a hydrophobic SiO2 nanoparticle sol;
[0034] S2, coating: coating the hydrophobic SiO2 nanoparticle sol obtained in step S1 on the glass substrate, and controlling the coating thickness to be 120 nm according to the pulling speed of the immersion coating apparatus. After coating, the glass sample is placed in an oven for drying. Example 1
[0035] This embodiment provides a method for preparing a wear-resistant and self-cleaning dual-function anti-reflection film, which specifically includes the following steps:
[0036] S1. Synthesis of hydrophobic SiO2 nanoparticles: 10 parts by mass of tetraethyl orthosilicate as silicon source, 80 parts by mass of anhydrous ethanol as solvent, 2 parts by mass of ammonia water as catalyst, 15 parts by mass of hexamethyldiazaine as hydrophobic modifier, SiO2 nanoparticles are prepared by hydrolysis polymerization, and then hexamethyldiazaine hydrophobic modifier is added, stirred for 3 hours, and then aged at room temperature for 7 days. Finally, hydrophobic SiO2 nanoparticles are obtained by centrifugation;
[0037] S2, preparing sol: dispersing 2.2 parts by mass of the hydrophobic SiO2 nanoparticles obtained in step S1 in a mixed solvent of 40 parts by mass of isopropanol and 20 parts by mass of methyl isobutyl ketone, stirring evenly, adding 0.12 parts by mass of pentaerythritol triacrylate and 0.1 parts by mass of hydroxycyclohexyl phenyl ketone. Stir evenly to obtain a composite sol;
[0038] S3, coating: the composite sol obtained in step S2 is coated on the glass substrate, and the coating thickness is controlled to be 115nm according to the pulling speed of the immersion coating apparatus. After the coating is completed, the glass sample is placed in an oven for drying. Finally, the sample is placed in a N2 purge chamber to make the O2 concentration lower than 100 ppm, and the O2 concentration is 400 mJ / cm 2 UV curing coating. Example 2
[0039] S1. Synthesis of hydrophobic SiO2 nanoparticles: 10 parts by mass of tetraethyl orthosilicate as silicon source, 80 parts by mass of anhydrous ethanol as solvent, 2 parts by mass of ammonia water as catalyst, 15 parts by mass of hexamethyldiazaine as hydrophobic modifier, SiO2 nanoparticles are prepared by hydrolysis polymerization, and then hexamethyldiazaine hydrophobic modifier is added, stirred for 3 hours, and then aged at room temperature for 7 days. Finally, hydrophobic SiO2 nanoparticles are obtained by centrifugation;
[0040] S2, preparing sol: dispersing 2.2 parts by mass of the hydrophobic SiO2 nanoparticles obtained in step S1 in a mixed solvent of 40 parts by mass of isopropanol and 20 parts by mass of methyl isobutyl ketone, stirring evenly, adding 0.18 parts by mass of pentaerythritol triacrylate and 0.15 parts by mass of hydroxycyclohexyl phenyl ketone. Stir evenly to obtain a composite sol;
[0041] S3, coating: the composite sol obtained in step S2 is coated on the glass substrate, and the thickness of the coating is controlled to be 120 nm according to the pulling speed of the immersion coating apparatus. After the coating is completed, the glass sample is placed in an oven for drying. Finally, the sample is placed in a N2 purge chamber to make the O2 concentration lower than 100 ppm, and the O2 concentration is 400 mJ / cm 2 UV curing coating. Example 3
[0042] S1. Synthesis of hydrophobic SiO2 nanoparticles: 10 parts by mass of tetraethyl orthosilicate as silicon source, 80 parts by mass of anhydrous ethanol as solvent, 2 parts by mass of ammonia water as catalyst, 15 parts by mass of hexamethyldiazaine as hydrophobic modifier, SiO2 nanoparticles are prepared by hydrolysis polymerization, and then hexamethyldiazaine hydrophobic modifier is added, stirred for 3 hours, and then aged at room temperature for 7 days. Finally, hydrophobic SiO2 nanoparticles are obtained by centrifugation;
[0043] S2, preparing sol: dispersing 2.2 parts by mass of hydrophobic SiO2 nanoparticles obtained in step S1 in a mixed solvent of 40 parts by mass of isopropanol and 20 parts by mass of methyl isobutyl ketone, stirring evenly, adding 0.06 parts by mass of pentaerythritol triacrylate and 0.05 parts by mass of hydroxycyclohexyl phenyl ketone. Stir evenly to obtain a composite sol;
[0044] S3, coating: the composite sol obtained in step S2 is coated on the glass substrate, and the thickness of the coating is controlled to be 116 nm according to the pulling speed of the immersion coating apparatus. After the coating is completed, the glass sample is placed in an oven for drying. Finally, the sample is placed in a N2 purge chamber to make the O2 concentration lower than 100 ppm, and the O2 concentration is 400 mJ / cm 2 UV curing coating.
[0045] Figure 2 (a) is a transmission electron micrograph of the SiO2 nanoparticles prepared in Comparative Example 2. Figure 2 (b) is a scanning electron microscope photograph of the SiO2 nanoparticle coating prepared in Comparative Example 2.
[0046] Figure 3 (a) is a transmission electron microscope photograph of the sol prepared in Example 1. Figure 3 (b) is a scanning electron microscope photograph of the coating prepared in Example 1.
[0047] from Figure 2 and Figure 3 It can be seen that the particle coating prepared in Example 1 is wrapped and connected by the organic polymer, while in Comparative Example 1, the coating is formed by random accumulation of nanoparticles.
[0048] Figure 4 1 is the transmittance spectrum of the anti-reflection films prepared in Example 1, Example 2 and Example 3. It can be seen that after the coating is applied on the glass substrate, they all show excellent anti-reflection performance. Among them, Example 1 has the best anti-reflection effect, and the peak transmittance reaches 99.1%, which is close to the anti-reflection effect of the best anti-reflection film on the existing single-layer glass substrate.
[0049] Figure 5 (a) and (b) are respectively the scratches of a 3H hardness pencil on the coatings prepared in Comparative Example 2 and Example 1 observed under an optical microscope. It can be seen that the scratches of the coating prepared in Comparative Example 2, i.e., the coating directly prepared with hydrophobic SiO2 nanoparticles, under a 3H hardness pencil are deep, while the scratches of the coating prepared in Example 1 under a 3H hardness pencil are shallow, which indicates that the presence of the organic polymer can significantly improve the mechanical properties of the coating.
[0050] Figure 6 The water contact angle test results of the coatings prepared in Comparative Example 1, Comparative Example 2, Example 1, Example 2 and Example 3 show that the water contact angle of the coating prepared in Comparative Example 1 is about 3.2°, while the water contact angle of the coating prepared in Comparative Example 2 is 136°, and the water contact angle of Example 1 is 118°. This shows that the coating prepared in Example 1 is hydrophobic, so that the coating has self-cleaning properties.
[0051] It can be seen from the experimental results of the above comparative examples and embodiments that the present invention prepares an anti-reflection film with dual functions of wear resistance and self-cleaning.
[0052] Those skilled in the art should understand that the above are only some specific embodiments of the present invention, rather than all embodiments. It should be noted that for those of ordinary skill in the art, many modifications and improvements can be made, and all modifications or improvements that do not exceed the scope of protection of the present invention should be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a wear-resistant, self-cleaning anti-reflection film, characterized in that: The steps include: S1. Synthesis of hydrophobic SiO2 nanoparticles: SiO2 nanoparticles are prepared by hydrolysis polymerization using tetraethyl orthosilicate as a silicon source, anhydrous ethanol as a solvent, ammonia water as a catalyst, and hexamethyldiazaine as a hydrophobic modifier, and then the hexamethyldiazaine hydrophobic modifier is added and stirred for 3-6 hours, and then aged at room temperature for 7-14 days, and finally, centrifuged to obtain hydrophobic SiO2 nanoparticles; S2, preparing sol: dispersing the hydrophobic SiO2 nanoparticles obtained in step S1 in a mixed solvent of isopropanol and methyl isobutyl ketone, stirring evenly, adding pentaerythritol triacrylate and hydroxycyclohexyl phenyl ketone, and stirring evenly to obtain a composite sol; S3, coating: coating the composite sol obtained in step S2 on a glass substrate, controlling the coating thickness according to the pulling speed of the immersion coating apparatus, and after coating, drying the glass sample in an oven. Finally, placing the sample in a N2 purge chamber to make the O2 concentration lower than 100 ppm, using 400 mJ / cm 2 UV-curable coatings, where the coating is cured under UV light and turns into an organic polymer; The addition amounts of tetraethyl orthosilicate, ammonia water, anhydrous ethanol, and hexamethyldiazaalkane in step S1 are 5-15 parts by mass, 1-5 parts by mass, 60-100 parts by mass, and 10-30 parts by mass, respectively; The added amounts of the hydrophobic SiO2 nanoparticles, isopropyl alcohol, methyl isobutyl ketone, pentaerythritol triacrylate and hydroxycyclohexyl phenyl ketone in step S2 are 1-4 parts by mass, 20-50 parts by mass, 10-30 parts by mass, 0.01-0.5 parts by mass and 0.01-0.2 parts by mass, respectively.
2. The method for preparing a wear-resistant, self-cleaning anti-reflection film according to claim 1, characterized in that: The pentaerythritol triacrylate and hydroxycyclohexyl phenyl ketone in step S2 are respectively UV-curable acrylate resin and polymerization photoinitiator.
3. The method for preparing a wear-resistant, self-cleaning anti-reflection film according to claim 1, characterized in that: The coating thickness described in step S3 is 80-140 nm.
4. The method for preparing a wear-resistant, self-cleaning anti-reflection film according to claim 1, characterized in that: The volume ratio of hydrophobic SiO2 nanoparticles to organic polymer in the coating is 8:
2.
5. The method for preparing a wear-resistant, self-cleaning anti-reflection film according to claim 1, wherein the size of the hydrophobic SiO2 nanoparticles is 10-80 nm.
6. A wear-resistant, self-cleaning anti-reflection film prepared by the preparation method according to any one of claims 1 to 5.
Citation Information
Patent Citations
Anti-fouling flame-retardant coating composition and preparation method thereof, and anti-fouling flame-retardant film
CN115124872A
Toner
CN117270347A